Gender and demand stimulation for agricultural mechanization service use in Ethiopia - Jaleta, Moti; Mohammed, Abdu; Gebresilasse, Mesay; Godlonton, Susan (International Maize and Wheat Improvement Center, 2023)
Agricultural mechanization is less developed in subSaharan Africa (SSA). Even in areas where there are scale-appropriate mechanization services, their use by smallholders (especially by women farmers) is minimal due to various social and economic factors. Following a randomized control trial (RCT) approach in stimulating men and women farmers in machinery-service use for cereals threshing and collecting survey data from 841 women-headed and 1,116 men-headed households in East and Southwest Shewa Zones in Central Ethiopia, this paper assesses how gender of the household head affects the demand for mechanization services. Empirical results show that gender of a household head is associated with the use of machinery services. Younger household heads are more proactive in using incentives provided in stimulating machinery-service use for threshing. Regardless of the gender of household heads, there is a location difference on the intensity of mechanizationservice use by smallholders. In most of the cases, the size of the cultivated farmland matters in mechanizationservice use. Overall, subsidies have a significant effect in stimulating demand for mechanization services by smallholders. However, no significant difference was observed between men and women household heads in using the provided incentives for demand stimulation. This implies that availability of mechanization services alone does not guarantee use of these services by men and women farmers. It is essential to further explore the role of institutional setups in which smallholder farmers operate and the supply side challenges service providers have in reaching out to men and women farmers under poor rural infrastructure.